Response of Submerged Macrophyte Growth, Morphology, Chlorophyll Content and Nutrient Stoichiometry to Increased Flow Velocity and Elevated CO2 and Dissolved Organic Carbon Concentrations - Reitsema, Rosanne E.; Wolters, Jan-Willem; Preiner, Stefan; Meire, Patrick; Hein, Thomas; De Boeck, Gudrun; Blust, Ronny; Schoelynck, Jonas (Frontiers in Environmental Science, 2020)
It is expected that climate change will cause more frequent extreme events of heavy precipitation and drought, changing hydrological conditions in riverine ecosystems, such as flow velocity, evapotranspiration (drought) or runoff (heavy precipitation). This can lead to an increased input of terrestrial organic matter and elevated levels of dissolved organic carbon (DOC) and CO2 due to degradational processes in water. Consequences for submerged macrophytes, as essential organism group, are still poorly understood. The combined effects of changing flow velocity, DOC and CO2 have not been studied before, so this was tested in a racetrack flume experiment on the macrophyte Berula erecta using a trait-based approach. The plants were exposed to two different flow velocities, two DOC concentrations and two CO2 concentrations in a full factorial design. Apart from individual dose-response tests, two climate change scenarios were tested: a wet scenario simulating heavy precipitation and runoff with high flow velocity, high DOC and CO2 concentrations and a dry scenario simulating evapotranspiration with low flow velocity, high DOC and high CO2 concentrations. Growth rate, biomass, morphology, chlorophyll and nutrient content (C, N and P) were measured. B. erecta responded strongly to both scenarios. Biomass and the relative growth rate increased and stems were shorter, especially in the wet scenario, and vegetative reproduction (the number of stolons) decreased. In both scenarios, the N content was lower and P content higher than in conditions without climate change. It can be concluded that climate change effects, especially shading by DOC, strongly influence macrophytes: macrophyte abundance will probably be negatively affected by climate change, depending on the macrophyte species and abundance of epiphytic algae. This may have consequences for other components of the aquatic ecosystem.